2004
DOI: 10.1088/0960-1317/14/11/012
|View full text |Cite
|
Sign up to set email alerts
|

Design and fabrication of tungsten carbide mould with micro patterns imprinted by micro lithography

Abstract: Core fabrication is one of the key technologies of glass moulding process used in micro optical component manufacturing. However, when the cavity size is very small and an array-type cavity is needed, a conventional diamond turning process cannot be employed. In this study, a novel core fabrication method that can be used for glass micro optical components has been developed. First, microlens array (with individual lens diameters of 36–300 µm) mould masters were produced with silicon using a photoresist reflow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Pure ultrafine (UF) WC powder has recently attracted an increased interest in the hard-metal industry due to its potential advantages, related to its unique properties suitable for a wide range of advanced applications such as dies for aspherical glass lens forming [7], microdies [8][9][10] and electrodes for micro-electro-discharge machining. The current demand for UF carbide manufacture is mainly driven by the need for increasing hardness, wear resistance and toughness.…”
Section: Introductionmentioning
confidence: 99%
“…Pure ultrafine (UF) WC powder has recently attracted an increased interest in the hard-metal industry due to its potential advantages, related to its unique properties suitable for a wide range of advanced applications such as dies for aspherical glass lens forming [7], microdies [8][9][10] and electrodes for micro-electro-discharge machining. The current demand for UF carbide manufacture is mainly driven by the need for increasing hardness, wear resistance and toughness.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, He et al [ 24 ] reported the fabrication of a silicon (Si) mold with microstructures fabricated using lithography and reactive ion etching (RIE) for optical glass molding. In addition, Choi et al [ 25 ] developed a tungsten carbide (WC) mold with microlens (ML) patterns via a sintering and polishing process, while Xie et al [ 26 ] studied a nickel–phosphorous (Ni–P) alloy mold with a microgroove structure produced using electroforming and micromachining techniques. Lee et al [ 27 ] described the fabrication of a glassy carbon (GC) mold with a microchannel pattern that was produced using micromachining in an electrolytic medium.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely applied as mold materials and wear resistant parts. More and more molds are made of cemented carbide instead of steel to fulfill the demands of long mold life and high product quality [ 3 , 4 , 5 ]. Micromechanical cutting can produce miniature parts that have three-dimensional features such as narrow grooves, microcavities, and an aspheric surface [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%